Descriptive study on the impact of material migration on the well-being of children left behind. - Arcete, Cheryl P.; Parcon, Cristabel Rose (2016.)
This study is quantitative which sought to describe the nature of the relationship of migrant mothers and students who are children left-behind; to describe the well-being of students in terms of their academic performance, social well-being and family relationships; and to identify problems encountered by students related to having migrant mothers. Family systems theory was used as the framework in this study, to better understand and explain the impact of maternal migration on the well-being of children left-behind. Thirty (30) students of the UPV CAS were chosen as respondents, through snowball sampling method, to participate in the face-to-face survey. Respondents were given survey questionnaires that comprised questions pertaining: (1) respondent?s profile, (2) migrant mother?s profile, (3) relationship with migrant mother, (4) well-being (problems, added responsibilities, relationship with other family members) and (5) their risk-taking behaviours. The data was analyzed through the use of Statistical Package for Social Science (SPSS). Results showed that there is a significant relationship between academic performance and sex of the respondents, as well as the length of stay of migrant mothers. Furthermore, children left-behind experience difficulties which vary depending on their birth order. Thus, maternal migration affects the well-being of children left-behind, however, are able to maintain and improve their academic performance. Additionally, their mother?s absence makes them vulnerable to risky behaviours, as well as encounter financial and academic problems. Maternal migration lead children left-behind to cater unfulfilled roles and take part in major decisions in family matters.
Research Project (Undergraduate, Bachelor of Arts in Sociology) College of Arts and Sciences, University of the Philippines in the Visayas.
Keywords: Children -- Left Behind; Mothers -- Migrant